IMPLEMENTASI PRAKTIK AKUNTANSI BERKELANJUTAN UNTUK UMKM: STUDI KASUS PADA KAWASAN KULINER CENTRAL POINT INDONESIA (CPI) MAKASSAR - Andi Faisal; Adriansyah Adriansyah; Anisatun Humayrah Rais; Yulia Yunita Yusuf; Chris Dayanti Br. Ginting S (Jurnal Akademik Pengabdian Masyarakat Ichsan Sidrap, 2024)
Sustainable accounting practices are becoming increasingly relevant as awareness of sustainability grows in all aspects of business, including the Micro, Small, and Medium Enterprises (MSME) sector. This article examines the implementation of sustainable accounting practices in MSMEs within the culinary area of Central Point Indonesia (CPI) Makassar using the Focus Group Discussion (FGD) method. The objective of this community service activity is to identify the benefits, challenges, and impacts of adopting sustainable accounting practices in MSMEs and to understand how a collaborative approach can enhance the capacity of MSME actors in sustainable financial management. The findings from this activity reveal that although challenges related to accounting knowledge and resource limitations remain significant barriers, the application of sustainable accounting can improve operational efficiency and support business sustainability. Collaborative mentoring between researchers and MSME actors is a key factor in the successful implementation of these practices. The implications of this community service indicate that optimizing the adoption of sustainable accounting in the MSME sector requires ongoing efforts in education, training, and technological support, as well as policies that promote business sustainability at the micro level.